2022
DOI: 10.1155/2022/5581346
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Attenuates the ECM Degradation and Oxidative Stress of Chondrocytes through the Nrf2/NQO1/HO‐1 Pathway to Ameliorate Rat Osteoarthritis

Abstract: Osteoarthritis (OA) substantially reduces the quality of life of the elderly. OA therapy remains a challenge since no treatment options for its causes are so far available. Over recent years, researchers have speculated that emodin may represent a potential treatment strategy for OA. However, it remains unclear whether the mechanism of action of emodin is associated with the inhibition of OA-induced oxidative stress. In the present study, the potential antioxidant mechanism of action of emodin and its protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These proteins scavenge free radicals and protect cells against oxidative stress through various molecular pathways. 87 Thus, Nrf2 activation is a key target for endothelial protective activity against oxidative stress. Zhou et al (2021) showed that CR synergistically induced Nrf2 translocation, 60 which then exhibited increased expressions of HO-1, SOD and NAD, leading to reduced ROS and apoptosis in EA.hy926 cells.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins scavenge free radicals and protect cells against oxidative stress through various molecular pathways. 87 Thus, Nrf2 activation is a key target for endothelial protective activity against oxidative stress. Zhou et al (2021) showed that CR synergistically induced Nrf2 translocation, 60 which then exhibited increased expressions of HO-1, SOD and NAD, leading to reduced ROS and apoptosis in EA.hy926 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis and aging may be caused primarily by excessive ROS production and an imbalance in antioxidant capacity, and the development of OA involves a variety of complicated pathogenic pathways, including apoptosis and ECM deterioration ( Yudoh et al, 2005 ; Hwang and Kim, 2015 ). As established in a prior research, we employed 0.4 mM H 2 O 2 as a ROS donor to trigger oxidative damage in chondrocytes in vitro ( Zheng et al, 2020 ; Ma et al, 2022b ). As expected, H 2 O 2 reduced chondrocyte viability, promoted inflammatory response and apoptosis, and increased cartilage matrix metabolism, whereas GC corrected these processes, demonstrating that it has a protective impact on chondrocytes exposed by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%